Getting the Most out of Bahiagrass Fertilization - Cheryl L. Mackowiak; Ann R. Blount; Edward A. Hanlon; Maria L. Silveira; Martin B. Adjei; Robert O. Myer (EDIS)
SL-249, a 6-page fact sheet by C. L. Mackowiak, A. R. Blount, E. A. Hanlon, M. L. Silveira, M. B. Adjei, and R. O. Myer, summarizes analysis practices and recommendations for bahiagrass fertilization for hay, sod or pasture systems. Includes recommended readings. Published by the UF Department of Soil and Water Sciences, April 2008.